The effects of the CNF ratio on the microstructure, corrosion, and mechanical properties of CNF-reinforced diamond cutting tool - Islak, Serkan; Ozorak, Cihan; Abouacha, Naser Matoug Emhmed; Caligulu, Ugur; Koc, Vahdettin; Kucuk, Ozkan (Elsevier Science Sa, 2021)
This study sets out to investigate the effects of CNF on the microstructure, corrosion, and mechanical properties of a carbon nanofiber (CNF)-reinforced diamond cutting tool matrix. First, CNF was added to bronze (i.e. the matrix) at different ratios (0, 0.25, 0.50, 0.75, and 1.00 wt%). Hot pressing was selected as the preferred method of production as it allows producing a larger number of compact samples. Next, the manufactured samples' microstructure, hardness, density, transverse rupture strength (TRS), corrosion, and wear properties were analysed. Then, their microstructures and phase compositions were examined using optical microscopy and XRD. Their hardness was measured using a microhardness device. Their TRS values were calculated using a three-point bending test. Their fractured surfaces were examined using SEM-EDS. Wear properties were examined using the reciprocating wear test. Their corrosion behaviours were analysed using potentiodynamic measurements. Optical microscope images showed that CNF exhibited flocculation in several areas along the bronze matrix. The samples' hardness increased significantly with higher CNF ratios, whereas their relative densities dropped slightly. The TRS reached its maximum value at 0.25% CNF. Beyond that, a significant drop was observed in TRS. The higher the samples' CNF ratios were, the less corrosion resistance they got due to the microgalvanic effect. The results of wear test showed that as the samples' CNF ratios rose, their wear rates and their friction coefficients incrementally dropped.
Keywords: CNF; Bronze; Diamond cutting tools; Microstructure; Mechanical property; Corrosion